Clinical Efficacy and Prognosis Study of Recurrent Laryngeal Nerve Anatomical Surgery on serum TNF-α, CRP, interleukins IL-6, IL-10, and IL-1β and outcomes: serum TNF-α, CRP, IL-6, IL-10, and IL-1β in Thyroidectomy - Cheng, Hui (Journal of Medical Biochemistry, 2025)
Introduction: This study aimed to evaluate the effects of recurrent laryngeal nerve anatomical exposure during thyroidectomy on serum TNF-α, CRP, interleukins IL-6, IL-10, and IL-1β, treatment outcomes, complications, and patient prognosis, with a specific focus on inflammatory and stress markers, including interleukins.Methods: A total of 110 patients with thyroid lesions undergoing thyroidectomy were randomly assigned to two groups: Expose (n=55), where the recurrent laryngeal nerve was exposed during surgery, and non-expose (n=55), where it was not. Various outcome measures were assessed, including surgical efficacy, vocal cord function, serum inflammatory and stress markers (TNF-α, CRP, interleukins IL-6, IL-10, and IL-1β), thyroid function changes, postoperative complications (including RLNI), and patient satisfaction. Additionally, quality of life (QoL) was evaluated.Results: The Expose group exhibited a smaller flap area and shorter hospital stays compared to the non-expose group, though the surgery took longer (P
Keywords: TNF-α, CRP, interleukins IL-6, IL-10, and IL-1β ,Thyroidectomy, Recurrent laryngeal nerve injury, Anatomical exposure, Vocal cord function, Inflammatory markers, Interleukins, Quality of life, Surgical satisfaction, Postoperative recovery.